Efektivitas Aplikasi DW Learn German Level A1 Pada Pembelajaran Siswa Kelas XI di SMA Negeri 15 Surabaya - Siburian, Vera Chentia; Titaley, Audrey Gabriella (LATERNE, 2024)
Abstract This study aims to evaluate the effectiveness of the DW Learn German Level A1 application in supporting German language learning among 11th-grade students at SMA Negeri 15 Surabaya. The background of this research lies in the increasing interest in the German language, particularly in Indonesia, which has directed the study's focus on the role of this application in improving students' German language skills. Data collection was conducted through a Google Forms-based questionnaire filled out by 36 students from class X-G1. The method used in this research is the System Usability Scale (SUS), designed to measure the usability level of a system or application, to assess the extent to which this application is effective in supporting German language learning. Based on data analysis, it was concluded that the DW Learn German Level A1 application falls into the "Marginal" category, indicating the need for quality improvements. The questionnaire results showed a final average score of 70.2. According to the SUS scale, scores ranging from 51.7 to 71 are categorized as "Marginal." With a SUS score of 70.2, the application is at the upper limit of this category. This indicates that although the application provides benefits to its users, several aspects still need to be improved to achieve a higher level of effectiveness. The aspects requiring improvement include enhancing ease of use, efficiency, responsiveness, and overall user satisfaction. However, this study has limitations, particularly in the scope of the sample size, the variety of evaluated aspects, and the application's alignment with German language learning methods at the high school level. Therefore, further research is needed to explore factors affecting user experience and identify specific areas that require improvement, so that the application can better meet user needs and expectations in the context of German language learning. Keywords: Effectiveness, Application, DW Learn German, System Usability Scale